I am looking at

$$A(x − h)^2 + B(x − h)(y − k) + C(y − k)^2 = 1$$

This is a rotating ellipse formula, where $h,k$ are the centroid of the ellipse. I have tried looking around for $A,B,C$ parameters, and I see that they are from Quadratic formula. But to be frank, I want to see how $A,B,C$ impact the orientation of the ellipse and I am looking for a more visual explanation for this question.

  • 2
    $\begingroup$ In the future, you may want to hold off on accepting an answer for a while, just so you don't need to keep changing your accepted answer as new answers are posted. :) $\endgroup$ – Rahul Dec 24 '12 at 7:32

I interpreted the question as asking for intuition about the parameters directly. So here is an alternative explanation. Of course, for doing anything useful with the ellipse, the eigenvalue/eigenvector perspective in Robert's answer is usually the most valuable, as it is coordinate-independent and more mathematically natural.

The ellipse is centered at the point $(h,k)$. It passes through the four points $(h\pm a,k)$ and $(h,k\pm c)$, where $a = 1/\sqrt A$ and $c = 1/\sqrt C$. That is, $A$ and $C$ tell you where the ellipse meets the horizontal and vertical lines through its center.

It's hard to say anything quantitative about the effect of $B$ without involving eigenvalues and eigenvectors, as in Robert's answer. Qualitatively, it controls how the ellipse deviates from being axis-aligned.

enter image description here

Above are three ellipses, each with $A=1/4$ and $C=1$, and with varying values of $B$. As you can see, all of them have the same span along the horizontal axis, $a = 1/\sqrt{1/4} = 2$, and similarly in the vertical, $c = 1/\sqrt 1 = 1$. When $B = 0$ (blue), the ellipse is axis-aligned. When it is positive ($B = 1/2$, maroon), the ellipse is oriented like a "\"; when it is negative ($B = -1/2$, yellow), it is oriented like a "/".

  • $\begingroup$ For the blue ellipse, ($ B = 0 $) why does its horizontal axis shorter than the other two ellipses? Is this correct? $\endgroup$ – Karl Dec 24 '12 at 7:39
  • $\begingroup$ Yes, the value of $a = 1/\sqrt A$ is not the half-width of the bounding box enclosing the ellipse, it is the point where the ellipse meets the horizontal axis. Observe that all three ellipses meet the horizontal axis $y=0$ at the same point. $\endgroup$ – Rahul Dec 24 '12 at 7:42
  • $\begingroup$ I've edited the image; maybe this makes it clearer. $\endgroup$ – Rahul Dec 24 '12 at 7:45
  • $\begingroup$ +1 (to Robert also). With a little bit of imagination one can `see' here that when $B\to-1+$ or $B\to1-$ (keeping $A,C$ fixed) the ellipse becomes more and more elongated and in a sense approach the union of two parallel lines. $\endgroup$ – Jyrki Lahtonen Dec 24 '12 at 10:37

The axes of the ellipse are in the directions of the eigenvectors of the $2 \times 2$ symmetric matrix $$M = \pmatrix{A & B/2\cr B/2 & C\cr}$$ which corresponds to the quadratic form: $$ A x^2 + B x y + C y^2 = (x\ y) M \pmatrix{x\cr y\cr}$$ The semi-major and semi-minor axes are then $\lambda^{-1/2}$ where $\lambda$ are the eigenvalues.

Thus suppose you want an ellipse with centroid at the origin (any other centroid, of course, can be obtained by translation), semi-axes $a$ and $b$ with the major axis at angle $\theta$ counterclockwise from the positive $x$ axis. The eigenvectors can be taken to be $\pmatrix{\cos \theta\cr \sin \theta\cr}$ and $\pmatrix{-\sin \theta\cr \cos \theta\cr}$ for eigenvalues $1/a^2$ and $1/b^2$ respectively, and then $$M = \pmatrix{\cos \theta & -\sin \theta\cr \sin \theta & \cos \theta\cr} \pmatrix{1/a^2 & 0\cr 0 & 1/b^2\cr} \pmatrix{\cos \theta & \sin \theta\cr -\sin \theta & \cos \theta\cr} $$ We get $A = \dfrac{\cos^2 \theta}{a^2} + \dfrac{\sin^2 \theta}{b^2}$, $B = \left(\dfrac{1}{a^2} - \dfrac{1}{b^2}\right) \sin(2\theta)$, $C = \dfrac{\sin^2 \theta}{a^2} + \dfrac{\cos^2 \theta}{b^2}$.


I would like to explain the transforms on a picture.

enter image description here


$$x=x'.\cos \alpha - y'. \sin \alpha $$

$$y=x'.\sin \alpha + y'. \cos \alpha $$

We can get easily the result above from the picture

$$\cos \alpha. x=\cos \alpha (x'.\cos \alpha - y'. \sin \alpha) $$

$$\sin \alpha. y=\sin \alpha (x'.\sin \alpha + y'. \cos \alpha) $$

$$x'=x.\cos \alpha + y. \sin \alpha $$

$$-\sin \alpha. x=\cos \alpha (x'.\cos \alpha - y'. \sin \alpha) $$

$$\cos \alpha. y=\sin \alpha (x'.\sin \alpha + y'. \cos \alpha) $$

$$y'=-x.\sin \alpha + y. \cos \alpha $$

$$\frac{(x.\cos \alpha + y. \sin \alpha)^2}{a^2}+\frac{(-x.\sin \alpha + y. \cos \alpha)^2}{b^2}=1$$

$$(\frac{\cos^2 \alpha }{a^2}+\frac{\sin^2 \alpha }{b^2})x^2+2(\frac{\cos \alpha \sin \alpha }{a^2}-\frac{\cos \alpha \sin \alpha }{b^2})xy+(\frac{\sin^2 \alpha }{a^2}+\frac{\cos^2 \alpha }{b^2})y^2=1$$

$$(\frac{\cos^2 \alpha }{a^2}+\frac{\sin^2 \alpha }{b^2})x^2+ \sin 2\alpha (\frac{1 }{a^2}-\frac{1}{b^2})xy+(\frac{\sin^2 \alpha }{a^2}+\frac{\cos^2 \alpha }{b^2})y^2=1$$

$$Ax^2+ Bxy+Cy^2=1$$



$$A(X-h)^2+ B(X-h)(Y-k)+C(Y-k)^2=1$$

$$A=\frac{\cos^2 \alpha }{a^2}+\frac{\sin^2 \alpha }{b^2}$$

$$B=\sin 2\alpha (\frac{1 }{a^2}-\frac{1}{b^2})$$

$$C=\frac{\sin^2 \alpha }{a^2}+\frac{\cos^2 \alpha }{b^2}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.